2013
DOI: 10.5194/acp-13-10919-2013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of organic aerosol produced during pulverized coal combustion in a drop tube furnace

Abstract: Abstract. Controlled bench scale pulverized coal combustion studies were performed, demonstrating that inorganic particles play a critical role as carriers of organic species. Two commonly-used aerosol mass spectrometry techniques were applied to characterize fine particle formation during coal combustion. It was found that the organic species in coal combustion aerosols have mass spectra similar to those generated by biomass combustion. Ambient measurements in Shanghai, China confirm the presence of these spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 57 publications
(91 reference statements)
9
55
0
Order By: Relevance
“…Pratt et al, 2009) or grouped aerosol particles as simply mixed or industrial (Pratt et al, 2010). Similar comments have been made by Wang et al (2013) about the incorrect apportionment of coal combustion particles in the atmosphere to biomass burning sources. In this study, we have provided the first direct evidence that combustion ash particles can nucleate ice in the immersion mode.…”
Section: Atmospheric Implications Of Combustion Ash Particles As Ice mentioning
confidence: 63%
See 1 more Smart Citation
“…Pratt et al, 2009) or grouped aerosol particles as simply mixed or industrial (Pratt et al, 2010). Similar comments have been made by Wang et al (2013) about the incorrect apportionment of coal combustion particles in the atmosphere to biomass burning sources. In this study, we have provided the first direct evidence that combustion ash particles can nucleate ice in the immersion mode.…”
Section: Atmospheric Implications Of Combustion Ash Particles As Ice mentioning
confidence: 63%
“…This has led to ∼ 8000 million tonnes of coal being consumed daily in coalfired power plants which are distributed all over the world (WCA, 2013). It is estimated that about 90 % of the fly ash is captured via different collection mechanisms such as electrostatic precipitators, fabric filters or bag houses, dust collectors, and other hybrid engineering systems like hot gas filtration systems (Bond et al, 2004;Wang et al, 2013;WCA, 2013). Nevertheless, sizeable quantities of these ash particles are emitted to the atmosphere as a result of inefficiencies associated with collection systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The averaged HOA 151 profile fro m the 7-to 10-factor solutions was used as the anchor profile for M E-2 due to the s mall d ifferences among the 152 different solutions. Additionally, the constraining CCOA profile for Dongguan is still under consideration because the mass 153 spectrum of BBOA was found to be very similar to that of CCOA, raising the concern that coal combustion particles might 154 have been incorrectly apportioned to bio mass burning sources (Wang et al, 2013). Furthermo re, an appropriate CCOA 155 anchor profile could not be obtained due to an increase in the unconstrained PMF factor number (see Figure S2) and because 156 few studies have reported a comparison of the CCOA profile to other PMF factors.…”
Section: Qingdao 150mentioning
confidence: 99%
“…BC and PAHs are mainly derived from incomplete combustion processes (Schmidt and Noack, 2000;White, 1985), and thus they were used as tracers for the POAs. In this study, the BC was directly measured by the AE-31, and the PAHs were quantified using the method developed by Bruns et al (2015) based on AMS data.…”
Section: Regression Analysis For Poa Tracersmentioning
confidence: 99%